The Tomato Transcription Factor SlNAC063 Is Required for Aluminum Tolerance by Regulating SlAAE3-1 Expression - Jin, Jian Feng; Zhu, Hui Hui; He, Qi Yu; Li, Peng Fei; Fan, Wei; Xu, Ji Ming; Yang, Jian Li; Chen, Wei Wei (Frontiers in Plant Science, 2022)
Aluminum (Al) toxicity constitutes one of the major limiting factors of plant growth and development on acid soils, which comprises approximately 50% of potential arable lands worldwide. When suffering Al toxicity, plants reprogram the transcription of genes, which activates physiological and metabolic pathways to deal with the toxicity. Here we report the role of a NAC transcription factor (TF) in tomato Al tolerance. Among 53 NAC TFs in tomato, SlNAC063 was most abundantly expressed in root apex and significantly induced by Al stress. Furthermore, the expression of SlNAC063 was not induced by other metals. Meanwhile, SlNAC063 protein was localized at nucleus and has transcriptional activation potentials in yeast. By constructing CRISPR/Cas9 knockout mutants, we found that slnac063 mutants displayed increased sensitivity to Al compared to wild-type plants. However, the mutants accumulated even less Al than WT plants, suggesting that internal tolerance mechanisms but not external exclusion mechanisms are implicated in SlNAC063-mediated Al tolerance in tomato. Further comparative RNA sequencing analysis revealed that only 45 Al-responsive genes were positively regulated by SlNAC063, although the expression of thousands of genes (1557 up-regulated and 636 down-regulated) was found to be affected in slnac063 mutants in the absence of Al stress. KEGG pathway analysis revealed that SlNAC063-mediated Al-responsive genes were enriched in “phenylpropanoid metabolism”, “fatty acid metabolism”, and “dicarboxylate metabolism”, indicating that SlNAC063 regulates metabolisms in respond to Al stress. Quantitative RT-PCR analysis showed that the expression of SlAAE3-1 was repressed by SlNAC063 in the absence of Al. However, the expression of SlAAE3-1 was dependent on SlNAC063 in the presence of Al stress. Taken together, our results demonstrate that a NAC TF SlNAC063 is involved in tomato Al tolerance by regulating expression of genes involved in metabolism, and SlNAC063 is required for Al-induced expression of SlAAE3-1.